2016
DOI: 10.1002/ams2.221
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics of non‐convulsive status epilepticus diagnosed by simplified continuous electroencephalogram monitoring at an emergency intensive care unit

Abstract: AimThe present study aimed to elucidate the clinical characteristics of non‐convulsive status epilepticus (NCSE) in patients with altered mental status (AMS).MethodsThis single‐center retrospective study comprised 149 patients who were hospitalized between March 1, 2015 and September 30, 2015 at the emergency intensive care unit (ICU) of the Kagawa University Hospital (Kagawa, Japan). The primary outcome was NCSE incidence. The secondary outcome was the comparison of duration of ICU stay, hospital stay, and a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 17 publications
1
6
0
Order By: Relevance
“…Stroke itself seems to be associated with a heightened risk of NCSE, with previous studies confirming stroke as the main cause of NCSE in their cohort (9). The overall prevalence of NCSE in our study population was 38.75%, which is in line with occurrence rates reported in previous studies that range from 14 to 45.3% (10)(11)(12)(13). We likewise found that there was a greater rate of NCSE in our cohort than in exclusively retrospective studies.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Stroke itself seems to be associated with a heightened risk of NCSE, with previous studies confirming stroke as the main cause of NCSE in their cohort (9). The overall prevalence of NCSE in our study population was 38.75%, which is in line with occurrence rates reported in previous studies that range from 14 to 45.3% (10)(11)(12)(13). We likewise found that there was a greater rate of NCSE in our cohort than in exclusively retrospective studies.…”
Section: Discussionsupporting
confidence: 91%
“…without NCSE. The use of antiepileptic drugs may explain this discrepancy (12). On the other hand, some scholars also believe that the different inclusion criteria for patients might yield different results, and etiology is the most important factor influencing prognosis.…”
Section: Limitations and Future Perspectivesmentioning
confidence: 99%
“…For these reasons, cEEG monitoring and assessment of NCSE during the induction, maintenance, and rewarming periods are indicated for all TTM patients (Figs. 4, 5) [86,91,92]. Seizures following cardiac arrest are associated with increased mortality [85,87,88].…”
Section: Detection Of Seizuresmentioning
confidence: 99%
“…CHB-MIT EEGs were collected from 22 patients (ages 1. [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19]. The waveforms were sampled at 256 Hz and included annotations of the seizure's start and end identified by neurophysiologists at CHB.…”
Section: Eeg Datamentioning
confidence: 99%
“…Non-convulsive seizures (NCS) are common in critically ill patients (8-50%) [1][2][3][4][5][6], and if untreated, are associated with high mortality (17-51%) [6][7][8]. Furthermore, effective treatment must be timely, as delayed treatment can lead to long term neurologic disability [9][10][11]. Many intensive care units (ICU) now perform continuous EEGs (cEEG) to monitor for NCS.…”
Section: Introductionmentioning
confidence: 99%